EVALUATION OF ADDITIVES USED TO INCREASE THE NUTRITIONAL EFFICIENCY IN CATTLE CULTURE - Machado, A. M. C.; Janini, A. P. R.; Vicente, E. F. (Revista Brasileira de Engenharia de Biossistemas, 2014)
Nowadays, the livestock sector needs and demands a high efficiency on production systems in order to ensure good profitability and competitiveness, such as the rational cattle for reach a better efficiency in food production, especially meat and milk. In this brief study, fundamental aspects of ruminant nutrition regarding the rumen microorganisms, and the use of different additives in order to improve the nutritional balance of the production of beef cattle will be addressed.